2014
DOI: 10.18488/journal.80/2014.1.1/80.1.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Direct Effects of Stubble Burning on Some Edaphic Characteristics of Coastal Plain Sands at Different Heating Intensities

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…No tillage coupled with straw return caused a significant increase in aggregateassociated carbon within all the aggregate fractions in the topsoil. Moreover, Edem et al [73] reported a higher coarse sand fraction in the burnt plot relative to the unburnt plot. Bulk density increases of 4% was found in soil burnt with 30 kg-m 2 of the dry biomass and a 9% increase was found in 90 kg-m 2 treatment.…”
Section: Effect On Soil Physical Propertiesmentioning
confidence: 97%
“…No tillage coupled with straw return caused a significant increase in aggregateassociated carbon within all the aggregate fractions in the topsoil. Moreover, Edem et al [73] reported a higher coarse sand fraction in the burnt plot relative to the unburnt plot. Bulk density increases of 4% was found in soil burnt with 30 kg-m 2 of the dry biomass and a 9% increase was found in 90 kg-m 2 treatment.…”
Section: Effect On Soil Physical Propertiesmentioning
confidence: 97%